Modeling of thermodynamic properties of (Fe-Ni-C, Fe-Cr-C) alloys using computational approach : DOI: 10.48129/kjs.20257 - shah, Waseem Ullah; Dil Faraz khan; Saeed Ullah Jan; Haiqing yin (Kuwait Journal of Science, 2023)
The paper shows the thermodynamic properties of alloys Fe-Cr-C, Fe-Ni-C system using modeling and simulation approach. The thermo-calc software with databases is utilized for calculations and results. The calculation shows alloying at (1900K-2000K) temperature range. The atmospheric pressure is kept constant 106 Pascal. The active phase at 1900K is liquid phase with 1.00 mass % for C compositions. The total Gibbs energy is found decreasing in the Fe-Ni-C system, which shows the stability of the system. The enthalpy and entropy of the system is found near linear relation with temperature raise and coupling properties.BCC of entropy is more responsive then BCC of enthalpy during alloying. The Fe-Ni-C shows negative deviations from Raoults law and corresponding positive deviations from vegard, s and Henry law. The withstanding phase is graphite with highest thermal expansion coefficient. The highest T-zero fluctuations is noted in the Fe-Cr-C system. The alloy shows the less solubility of the carbon at low temperature, while results the great alloying at higher temperature in the Fe-Ni-C system better industrial aspects.